Numerical Method of Flexible Pavement considering Moisture and Stress Sensitivity of Subgrade Soils - Jue Li; Jianlong Zheng; Yongsheng Yao; Junhui Zhang; Junhui Peng (Advances in Civil Engineering)
Weaknesses of the subgrade structure induce the asphalt surface diseases and shorten the service life of flexible pavement. However, the resilient modulus (Mr) of subgrade soils is difficult to be evaluated directly since the subgrade is hidden and covered by the granular or asphalt layer. This study aimed to establish a numerical approach to predict the dynamic behavior of flexible pavements considering the stress sensitivity and moisture variation of subgrade soils. Firstly, 2D FEM simulations of flexible pavements were performed with half-sine loadings. A constitutive model of subgrade soils was proposed to incorporate soil suction and octahedral shear stress. It was validated using the laboratory triaxial test data of 3 selected soils. Then, the developed model was programmed by the user-defined material subroutine (UMAT) in the software ABAQUS. Subsequently, the validity of FEM model was verified by the laboratory tank model. Finally, the effect of moisture contents on the dynamic response of pavement structures was studied by tensile stress and vertical compressive strain. Results show that the surface deflection of the FEM model is similar to that of the actual pavement structure with the R2 of 98.44%. The developed UMAT program is reliable since the distribution of Mr in the FEM model is influenced by the stress and moisture condition of subgrade soils. When the moisture content is increased by 63%, the average Mr of subgrade soils is decreased by 18.7%. Meanwhile, the stiffness softening of subgrade soils increases vertical compressive strain at the top of the subgrade and the tensile stress at the bottom of the surface layer. It is interesting that the developed model can be applied to analyze the fatigue cracking of both subgrade and surface layers in the future.